A Foot-Shaped Amulet Stamp Found in Küllüoba (Eskişehir) - Türkteki, Murat (Fırat Üniversitesi, 2023)
The subject of this study is a foot-shaped amulet stamp made of stone found in a pithos tomb in the cemetery area dated to the Early Bronze Age I Period in Eskişehir/Küllüoba. This amulet, which has a thorn-leaved plant motif on the stamp surface, is dated to the beginning of the Early Bronze Age. There is no data on the administrative and bureaucratic stsystem in the settlement, so the control and control mechanism has not yet been formed. Aforementioned amulet stamp is important in terms of being the earliest known example of this type in Anatolia. In this study, the amulet has been discussed in terms of its form, decoration, context and function and has been dated both according to relative chronology and according to the results of absolute dating methods. In addition, it has been tried to be positioned by comparing it with similar examples in Anatolia. The intended use, motifs and interconnections of these objects, which are used with different functions such as stamps, seals and amulets, are also evaluated by considering the examples from different time periods in the Levant, Mesopotamia, Anatolia, Aegean World and Egypt in terms of chronology and interregional communication networks. The example of Küllüoba, which is the earliest known example in Anatolia so far, constitutes important data in terms of the relations of central and western Anatolia with the southern regions, especially in the context of the Levant and Northern Syria.

Eskişehir/Küllüoba’da İlk Tunç Çağı I Dönemi’ne tarihlenen mezarlık alanında bir pithos mezar içerisinde bulunmuş olan taştan yapılmış ayak biçimli bir amulet damga, bu çalışmanın konusunu oluşturmaktadır. Damga yüzeyi üzerinde diken yapraklı bir bitki motifi bulunan bu amulet, yerleşmede idari ve bürokratik yapılanma ile ilgili herhangi bir verinin olmadığı, dolayısıyla kontrol ve denetim mekanizmasının henüz oluşmadığı İlk Tunç Çağı’nın başına tarihlenmektedir. Söz konusu amulet, Anadolu’da bulunan bu tip amuletler içerisinde şimdilik bilinen en erken örnek olması açısından önem taşımaktadır. Bu çalışmada amulet; formu, bezemesi, konteksti ve işlevi açısından ele alınmış olup hem göreli kronolojiye göre hem de mutlak tarihlendirme yöntemlerinin sonuçlarına göre tarihlendirilmiştir. Bununla birlikte Anadolu’daki benzer örneklerle karşılaştırılarak da konumlandırılmaya çalışılmıştır. Bu doğrultuda Levant, Mezopotamya, Anadolu, Ege Dünyası ve Mısır’da farklı zaman dilimlerine ait örnekler üzerinden kronoloji ve bölgelerarası iletişim ağları açısından da ele alınarak damga, mühür ve amulet olmak üzere farklı işlevlerle kullanılan bu nesnelerin kullanım amaçları, motifler ve birbirleri ile olan bağlantıları da değerlendirilmiştir. imdilik Anadolu’da bilinen en erken örneği oluşturan Küllüoba örneği Orta ve Batı Anadolu’nun özellikle Levant ve Kuzey Suriye bağlamında güney bölgeler ile ilişkileri bakımından önemli bir veri oluşturmaktadır.
ESKİŞEHİR KÜLLÜOBA’DA BULUNAN AYAK BİÇİMLİ BİR AMULET DAMGA